Pengujian rancang ulang website perpustakaan Universitas Kristen Duta Wacana - Sophie, Simfony; Proboyekti, Umi; Wibowo, Argo (AITI, 2024)
The library website is a portal for students to access library services and resources. The library has never conducted an evaluation or assessment of its website. The initial observations show that some content and features on the library website should meet academic library website standards. This study aims to redesign the interface of the UKDW library website to accommodate student needs and meet the standards of the academic library website. The method used in this study is User Centered-Design (UCD), and the research stages included data collection, analysis, prototype design, and testing involving students and librarians. The testing phase applies the usability testing method. Usability testing was conducted twice, i.e., formative testing and summative testing. The result of this study is that the redesigned library website interface has been tested with the value of effectiveness, efficiency, and user satisfaction in the good category.